2008
DOI: 10.1002/ajim.20604
|View full text |Cite
|
Sign up to set email alerts
|

Fatalities in the landscape and horticultural services industry, 1992–2001

Abstract: Landscaping workers are at increased risk of fatal injury. Further research is needed to characterize industry hazards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…An extensive study by the Kauffman-Rand Institute found that, although small businesses have lower reported injury rates than larger businesses, they have higher fatality rates than larger businesses in the same industry (Mendeloff et al, 2006). Other studies of specific industries including landscaping and retail support this finding (Buckley et al, 2008;Peek-Asa et al, 1999). There is therefore a need to explore prevention strategies for smaller businesses.…”
Section: Introductionmentioning
confidence: 79%
“…An extensive study by the Kauffman-Rand Institute found that, although small businesses have lower reported injury rates than larger businesses, they have higher fatality rates than larger businesses in the same industry (Mendeloff et al, 2006). Other studies of specific industries including landscaping and retail support this finding (Buckley et al, 2008;Peek-Asa et al, 1999). There is therefore a need to explore prevention strategies for smaller businesses.…”
Section: Introductionmentioning
confidence: 79%
“…In fact, all of the studies identified from the literature review related primarily to worker fatalities. (3)(4)(5) This study provides a unique contribution to the literature by evaluating personal behaviors and perception of wearing protective gear among workers in this industry. This adds value to the existing occupational safety literature as well as serving as a reference for the area of behavioral research.…”
Section: Discussionmentioning
confidence: 99%
“…(3) Over the past 20 years, the job fatality rate has been higher when compared with other dangerous industries, and the differences have been increasing. (4) During 2003-2008, an average of 190 deaths occurred each year among commercial landscaping and grounds maintenance workers, accounting for 3.4% of total occupational fatalities in the United States.…”
mentioning
confidence: 98%
“…Research shows that the smaller the company, the higher the fatality rate for their workers is likely to be. In addition to oil and gas, this has been shown to be the case in construction (Buskin 1987;Derr, Forst et al 2001), mining (National Institute for Occupational Safety and Health 2008), landscape and horticultural services (Buckley, Sestito et al 2008), and logging (Scott 2004). Research shows that the type of extraction company also plays a factor in fatality rates.…”
Section: Introductionmentioning
confidence: 95%